Contemplative Epistemology in the Work of Sarah Coakley - Maxey, Amy (2024)
This paper explores and evaluates how Sarah Coakley conceives of contemplation as epistemology. Focusing on the internal logic of her account as she gives it, I argue that Coakley articulates an account of contemplative noesis as fundamentally affective, intuitive, and ‘nonrational’ which, upon critical examination, renders an ambiguous contemplative epistemology.